Influence of Trust, Risk Perception, and E-Service Quality on E-Commerce Consumer Purchase Intentions in Indonesia - Agustintia, Dwinda; Hayu, Rina Suthia; Putri, Seprianti Eka (UNIB Press, 2026)
The purpose of this study is to find out empirically the effect of trust, perceived risk and e-service quality on intention to purchase of online shop’s customers in Indonesia. This research is a type of descriptive research with a quantitative approach. The type of data used is primary data obtained through the distribution of questionnaires. Respondents of this study were online consumers in Indonesia which were taken by accidental sampling technique as many as 333 peoples. The data analysis method used descriptive analysis and partial least square (PLS) analysis. Based on field research, the results obtained are: (1) Trust has a positive and significant effect on intention to purchase of online shop consumer; (2) Perceived risk has a positive and significant effect on intention to purchase of online shop consumer; and (3) E-service quality has a positive and significant effect on intention to purchase of online shop consumer. The implications of the research are the importance of trust aspects, risk perception and quality of electronic services to online transactions. It is expected that e-commerce vendors can provide a comprehensive guarantee that sellers who join their vendors can be trusted, transactions made safe and comfortable and services provided quality.